Otimização de métricas de rede de operadora de telecomunicações com roteamento por segmentos e engenharia de tráfego - Silvério, Antonio José (2019)
Currently, telecommunication operators’s main problems include managing and configuring a large number of tunnels in the IP/MPLS network edge and core routers, resulting an increasing of router flow states, and also a complexity of control protocol maintenance, and optimization of network resources with different metrics. In this scenario, dynamic changes and network failures requires constantly a manual tunnel planning and reconfiguration to a predictable controlled traffic routing. In this sense, segment routing is a technology that simplifies routing and the configuration of these networks. Segment routing is accomplished by combining segments that finds a path for traffic demands, however, segments can be reused, reducing the number of states in the network. Thus, this thesis formulates a two-step optimization problem, considering a backbone network with segment routing and traffic engineering. The model has the purpose of distributing traffic flows considering the link load and different traffic engineering parameters established by the telecommunications operator, minimizing the number of states or segments per router. Results based on real examples are presented, demonstrating the state-of-the-art model benefits of current segment routing modeling proposals, such as addressing multiple network metric objectives.